Religious Moderation: A Systematic Literature Review - Damopolii, Muljono; Umar, M. Shabir; Burga, Muhammad Alqadri; Awal, Muh. Idhul (Universitas Muhammadiyah Ponorogo, 2024)
This systematic review critically examines existing research on religious moderation, focusing on its nomenclature, typologies, and scope. The study employs the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to enhance transparency in the progression from data collection to article screening. The findings indicate that religious moderation, a strategic initiative of the Ministry of Religious Affairs of the Republic of Indonesia, encompasses the perspectives, attitudes, and behaviours of religious adherents. Its primary objective is to promote social harmony and foster inter- and intra-religious tolerance, thereby safeguarding the unity of the Republic of Indonesia. A total of 21 studies were identified as meeting the inclusion criteria. The scope of research on religious moderation is classified into five distinct scholarly domains: (1) education, (2) social sciences, (3) communication studies, (4) organizational culture, and (5) history. The study underscores the imperative for coordinated efforts between the Ministry of Religious Affairs and other governmental entities to mainstream religious moderation, mainly as institutions unaffiliated with the Ministry are at a higher risk of fostering radicalism. Additionally, future research should prioritize conducting empirical surveys on religious moderation within specific regions or institutions to generate evaluative data that will inform and support the Ministry’s strategic initiatives for embedding the values of religious moderation across diverse settings.